Análise filogeográfica do segmento genômico da proteína neuraminidase do H1N1 no Brasil - Martins, Junior Olimpio (Universidade Federal de São Carlos, 2022)
Seasonal flu, caused by Influenza viruses, is one of the most prevalent viral infections in the world, causing 290-650 thousand deaths annually. Such viruses, whose genome is composed of negatively oriented single-stranded RNA segments, have high mutational rates and the ability to rearrange between segments, allowing them to rapidly escape immune and even the emergence of pandemic strains. After the implementation of SINAN Influenza in Brazil in 2009, there was a large increase in the number of genomes sequenced and the unification of reported cases, allowing phylodynamic analyzes to be carried out on the sequences of the viruses collected in the country and their correlation with epidemiological data. During the present Course Completion Work, the objective was to study the molecular evolution and epidemiology of the Influenza A H1N1 virus in Brazil, using the genomic segment that encodes neuraminidase as a model. Through this approach, it was possible: (i) to calculate the mutational rate of the segment (3.02 x 10-3 substitutions/site/year) in accordance with the existing literature; (ii) identify variations in population sizes correlated with flu seasons with an increase in the number of cases; and (iii) even identify the southern region as a seedbed of flu strains in 2009. These results, despite not including the impact of the rearrangement, provide important information about the epidemiology and evolutionary parameters of seasonal influenza A H1N1 in Brazil.
Phylogeographic analysis of the genomic segment of Neuraminidase of H1N1 in Brazil
Keywords: Gripe; Influenza A; Neuraminidase; Filogenética; Filogeografia; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::BIOLOGIA E FISIOLOGIA DOS MICROORGANISMOS::VIROLOGIA